International Electron Devices Meeting 1991 [Technical Digest]
DOI: 10.1109/iedm.1991.235459
|View full text |Cite
|
Sign up to set email alerts
|

Delta-doped complementary heterostructure FETs with high Y-value pseudomorphic In/sub 1/Ga/sub 1-y/As channels for ultra-low-power digital IC applications

Abstract: We report on the device and circuit performance of Delta-Doped Complementary Heterostructure Insulated Gate Field Effect Transistors (C-HIGFETs) which make use of a high lnAs mole fraction (y-value) pseudomorphic InyGal-yAs channel along with a subchannel deltadoped Si layer to adjust the n-HIGFET and p-HIGFET threshold voltages. Results are presented showing that increasing the y-value of the In Gal. As channel up to y = 0.25 enhances both the n-hGFl!T and the p-HIGFET device performance as evidenced by the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous studies of 1 pm gate length C-HIGFET devices and circuits have explored the dependence of the performance of these devices and circuits on the doping profile beneath the InGaAs channel and on the composition of the AIGaAs gate barrier (1)(2)(3)(4)(5). It hais been shown that a planar ndoped layer in the GaAs buffer region below the lnyGal-yAs channel can adjust the threshold voltages of n-and p-channel devices anld that it tends to reduce subthreshold leakage and output conductance of the p-channel device thus giving it much improved operating characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of 1 pm gate length C-HIGFET devices and circuits have explored the dependence of the performance of these devices and circuits on the doping profile beneath the InGaAs channel and on the composition of the AIGaAs gate barrier (1)(2)(3)(4)(5). It hais been shown that a planar ndoped layer in the GaAs buffer region below the lnyGal-yAs channel can adjust the threshold voltages of n-and p-channel devices anld that it tends to reduce subthreshold leakage and output conductance of the p-channel device thus giving it much improved operating characteristics.…”
Section: Introductionmentioning
confidence: 99%